Childhood - Tolstoy, Leo, graf, 1828-1910; Hogarth, C. J. (Charles James), 1869-1942 (Salt Lake City, UT : Project Gutenberg, 2006)
"Childhood" by graf Leo Tolstoy is a novel published in 1852. It marks Tolstoy's debut at age twenty-three and launched his literary career, earning immediate acclaim from established Russian writers. The first in a trilogy followed by "Boyhood" and "Youth," it explores the inner world of young Nikolenka through an innovative expressionistic style that blends fact, fiction, and emotion. This groundbreaking work captures childhood's fleeting innocence, joy, and intense capacity for love through the narrator's moods and reactions. (This is an automatically generated summary.)
Translated from Russian title: Detstvo
Wikipedia page about this book: https://en.wikipedia.org/wiki/Childhood_(Tolstoy_novel)
Release date is 2006-03-22
Produced by Martin Adamson and David Widger
Keywords: Autobiographical fiction; Russia -- Social life and customs -- 1533-1917 -- Fiction; Tolstoy, Leo, graf, 1828-1910 -- Childhood and youth -- Fiction; Russia -- History -- 1801-1917 -- Fiction